KESULITAN-KESULITAN YANG DIALAMI SISWA KELAS XI PADA MATA PELAJARAN BORDIR JURUSAN DESAIN KRIA TEKSTIL DI SMK N 4 PARIAMAN - fitri, masra dona; zahri, wildati; rahmiati, rahmiati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
Abstract This reseach is purposed to describe the students‟ difficulties on embroidery subject at SMK Negeri IV Pariaman. The variables in thisresearch are difficulties that are faced by students of class XI inembroidery subject from textile skill design major at SMKN IVPariaman with indicators: 1) the knowledge of equipments andmaterials, 2) the basic technique of emroidery, 3) and the embroiderytechniques. This research is a kind of quantitative research withdescriptive method. The data analysing technique that is used by this method is percentage technique which purposes to see the students‟respond performance level toward the indicators. Based on the dataanalysis that is acquired about student difficulties on embroidery subjectconsist of: 1) the equipments and materials knowledge about embroiderysubject in textile skill design major at SMKN IV Pariaman is very high(80%), 2) the embroidery basic techniques of class XI students fromtextile skill design major at SMKN IV Pariaman is average (67,3%), 3)embroidery techniques of class XI students from from textile skill designmajor at SMKN IV Pariaman is high (70,8%). Kata Kunci: kesulitan-kesulitan,mata pelajaran bordir